Translation Procedure Applied in the Information Boards of Tegenungan Waterfall in Gianyar, Bali: A Study of Linguistics Landscape - Irwandika, Gede; I Made Perdana Skolastika (UHN IGB Sugriwa Denpasar, 2024)
This study aimed to describe translation procedures applied in the information Boards of Tegenungan waterfall in Gianyar, Bali, especially on bilingual information boards. The method used in this research was qualitative research to describe the translation procedures found on the information boards. Several theories were applied in this research: Landscape linguistics theory from Yendra and Artawa (2020), syntactic scope theory by Noortyani (2017), translation procedures by Vinay and Dalbernet (2000:84), and translation equivalence theory by Nida (2000). The analysis revealed that the information boards predominantly used literal translation, with some instances of adaptation and equivalence. Literal translation aimed to maintain the form and structure of the source language, ensuring clarity for both domestic and international visitors. However, there was room for improvement in linguistic accuracy and cultural nuances. By considering the principles of landscape linguistics and translation theory, authorities could enhance the quality of translation on the information boards. Improving the translations could lead to a more informative and engaging experience for visitors, contributing to their enjoyment and safety at Tegenungan Waterfall.